1996
DOI: 10.1001/archsurg.1996.01430140066018
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Translocation in Neonates and Infants Receiving Long-term Parenteral Nutrition

Abstract: In neonates and infants who are receiving PN, septicemia may be a gut-related phenomenon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
65
0
2

Year Published

2001
2001
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 103 publications
(69 citation statements)
references
References 26 publications
2
65
0
2
Order By: Relevance
“…Another factor that likely contributes to increased sepsis in LIT candidates is bacterial overgrowth and translocation. 16,17 Although graft and patient survival results after LITs are currently inferior to the results seen after isolated liver transplantations, they have steadily improved as the experience with the intestinal transplantation increases, 5 and the early progress of LITs is not unlike that encountered with other solid organ transplantations. 18,19 Since 1997, the vast majority of LIT candidate deaths (85%) have occurred in status 2B, 3, or 7 candidates (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Another factor that likely contributes to increased sepsis in LIT candidates is bacterial overgrowth and translocation. 16,17 Although graft and patient survival results after LITs are currently inferior to the results seen after isolated liver transplantations, they have steadily improved as the experience with the intestinal transplantation increases, 5 and the early progress of LITs is not unlike that encountered with other solid organ transplantations. 18,19 Since 1997, the vast majority of LIT candidate deaths (85%) have occurred in status 2B, 3, or 7 candidates (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Using molecular analysis, the authors provided genetic evidence that the strains isolated sequentially from cultures of stool, blood, and cerebrospinal fluid were identical. Pierro et al (46) studied neonates and infants receiving long-term parenteral nutrition. The authors found that six of 94 patients experienced 15 episodes of septicemia caused by bacteria of enteric origin; in all six patients, the causative organisms were also present in the throat or rectum.…”
Section: Discussionmentioning
confidence: 99%
“…They reported six infants with 15 episodes of septicaemia attributable to enteric organisms. 15 Availability of laboratories round the clock would have been an important factor and particularly in our study where most of the emergency cases were included. But it was not feasible in our study as culture was done during the working hours only.…”
Section: Post-op Sepsismentioning
confidence: 99%